Contingency analysis and reliability evaluation of Bangladesh power system - Ahmad, Shahriar; Zakaria, Nur Mohammad; Ashik-Ul-Elahi; Biswas, George Anindya Kumar (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.